2009
DOI: 10.21273/jashs.134.3.299
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Crop Load on Budbreak Influences Return Bloom in Alternate Bearing ‘Pixie’ Mandarin

Abstract: Alternate bearing trees produce a heavy (on) crop followed by a light (off) crop. Whereas it is well documented for citrus that fruit number in the current crop inversely affects flower number in the return bloom, when in the phenology of the tree and how fruit exert an effect on floral intensity the following spring remained unresolved. ‘Pixie’ mandarin (Citrus reticulata) was used as the model system to investigate when and how fruit perpetuate cyclic differences in floral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 12 publications
3
49
0
9
Order By: Relevance
“…Fruit maintained on the tree up to BBCH stage 79 or later significantly reduced the number of summer/autumn vegetative shoots that developed, thus reducing the number of branches on which to bear inflorescences the following spring, as has been shown in ‘Pixie’11 and ‘Nour’29 mandarin. Further, fruit removal also affects the number of nodes on these shoots, which in turn affects the number of flowers produced during spring bloom 11, 30…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Fruit maintained on the tree up to BBCH stage 79 or later significantly reduced the number of summer/autumn vegetative shoots that developed, thus reducing the number of branches on which to bear inflorescences the following spring, as has been shown in ‘Pixie’11 and ‘Nour’29 mandarin. Further, fruit removal also affects the number of nodes on these shoots, which in turn affects the number of flowers produced during spring bloom 11, 30…”
Section: Discussionmentioning
confidence: 64%
“…The effect of fruit inhibiting flowering has been shown in most polycarpic (perennial) fruit trees, both evergreen and deciduous species, such as apple and pear,20 peach14 and citrus,1 but none of those studies reported the exact moment when the fruit initiates its inhibitory effect. Recently, Verreynne and Lovatt11 provided evidence that removal of all fruit from ‘Pixie’ mandarin on‐crop trees early in summer increased total flower number in spring by increasing summer/autumn shoot number.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in more "synchronized," stronger summer flush growing on the hedged branches, perhaps regardless of differences in hedged branch age, physical dimensions, and position within the canopy. Summer flush growth is proven to be important in the return bloom (Verreynne and Lovatt, 2009). In contrast, in non-hedged parts of canopies, the summer BBU mostly appeared on previous spring growth flush.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological basis of the phenomenon in citrus lies in the inhibitory effect that the presence of fruit on a tree has on the initiation and/or the differentiation of flower buds for next season's crop, on budburst and on fruit set; the greater the size of the crop, the greater the effect (Moss, 1971;Muñoz-Fambuena et al, 2011;Verreynne and Lovatt, 2009). The effect is related more to the number of fruit, rather than the combined biomass of the fruit.…”
Section: Discussionmentioning
confidence: 99%